A TOGAF-based Framework for the Enterprise Architecture Development of Smart Digital Port: A Case of Container Port in Indonesia - Nurrosyidah, Afifah; Rachmannullah, Ashari Fitra (Politeknik STMI Jakarta, 2024)
Smart ports can be perceived as a viable solution to address the emerging complexities confronting international trade and logistics systems. Through the deep integration of digital technologies, including the Internet of Things, big data analytics, cloud computing, and artificial intelligence, smart ports stand to substantially enhance their capacity for intelligent operations and efficient resource allocation within port activities. In this paper, an architecture development using TOGAF with a case of Container Port A in Indonesia is conducted by analyzing the existing core business operation with smart port targeted. The development in business, information systems, and technology is discussed, and both existing problems and key research gaps in Container Port A are identified. As a result, main technology in automation and digital twin are needed with supporting information system and technology architecture. These innovations work together to create more efficient, automated, and interconnected port operations. By leveraging these technologies, smart ports can significantly enhance productivity, lower operational costs, and contribute to improved environmental sustainability within the maritime industry. The use of automation technology streamlines various operational processes, while tracing systems ensure accurate tracking and management of container. This synergy not only boosts efficiency but also promotes eco-friendly practices, aligning with the broader goals of Industry 4.0. However, further investigation to define the portfolio and feasibility study if initiatives is needed.